Rhetorical structure and metadiscourse markers of local and international agriculture research abstracts - Frelita Bartolome; WIlliam Magday (Universitas Ahmad Dahlan, 2026)
Educational mandates promoting a research culture among educators and students emphasize the importance of high-quality research publications. A critical component of this is writing effective research abstracts, a key requirement for journal acceptance. This comparative genre-based study aimed to analyze the macrostructure and linguistic features of 40 local agricultural research abstracts from a state university journal and 40 international abstracts from reputable journals covering 2011-2024. Using Hyland’s (2000, 2004, 2005) frameworks, the rhetorical structures, metadiscourse patterns, and communicative functions of the corpora were analyzed. Both local and international abstracts commonly employed moves like Purpose, Method, and Product. Local abstracts considered the Introduction and Conclusion moves as optional, while these moves were conventional in international abstracts. Typical patterns for local abstracts were PMPrC and PMPr, while most international abstracts followed Hyland's IPMPrC framework. Both sets used metadiscourse markers, but international abstracts employed them more frequently, favoring boosters over hedges to emphasize certainty and validation. These findings highlight the importance of adhering to international academic writing norms to enhance research visibility and impact, with implications for teaching academic writing and research.